Genetic diversity analysis of Katchaikatty Black – An endangered sheep breed from Tamil Nadu - ARORA, REENA; JAIN, ANAND; N, RAJA K; KAUR, MANDEEP; KUMAR, ASHISH; AHLAWAT, SONIKA; SHARMA, REKHA (The Indian Journal of Animal Sciences, 2023)
The study presents the genetic diversity of Katchaikatty Black, an endangered and culturally significant sheep breed of Tamil Nadu. A panel of 25 microsatellite markers recommended for Indian sheep was used for genotyping. Considerable genetic variation in terms of allele diversity and heterozygosity was observed within the investigated breed. A total of 174 distinct alleles were detected across the analyzed microsatellite loci with an average of 6.96 alleles per locus. The average observed and expected heterozygosity values were 0.600 and 0.706, respectively. The positive heterozygote deficiency (FIS) value of 0.171, estimated for this breed may be due to the possibility of Wahlund effect resulting from sampling from different breeding flocks, i.e. different villages and flocks in the same area. A normal L-shaped curve suggested absence of genetic bottleneck in this breed. The information generated will be useful in guiding conservation and management programmes for Katchaikatty Black sheep.